HISTORY OF THE TAJIKISTAN RAILWAY ORGANIZATION AND ITS ACTIVITIES (Scientific journal of the Fergana State University, 2026)
This article explores the formation and development of the railway system in the Republic of Tajikistan, focusing on the activities of the state enterprise "Tajik Railways" during the еars of independence. The main goal of the research is to identify the role of the railway system within the country’s transport infrastructure and assess its economic and geopolitical importance. The research methodology includes historical-analytical, comparative, and statistical approaches. The study draws upon archival materials, government decrees, official statistics, and international reports. The results demonstrate that the railway has played a significant role in facilitating Tajikistan’s foreign trade and regional transit connectivity. In conclusion, the modernization of infrastructure, deepening of regional integration, and improvements in logistical efficiency are emphasized as key priorities for sustainable development.